Learning with plants: didactic sequence of Botany for Elementary School II - Oliveira, Matheus Fernando Custódio de (2022)
The study of plants is as old as humanity itself. Studying them is essential to reduce the barriers of “botanical blindness” and “botanical illiteracy”, and these concepts are a result of the way Botany is taught in schools. To help overcome this, a didactic sequence of Botany through Teaching by Investigation was proposed for the 9th grades of Elementary School II in a municipal school in Araras/SP. For evaluation, a single questionnaire of four questions was used with the students in two moments: before and after classes. The results indicated that this is a plausible path, as it quadrupled the number of students who managed to make a valid relationship between a plant organ and its respective function in the plant. Therefore, this article shows that the teaching of Botany should be explored in different ways from the traditional one in order to reduce the gaps in Basic Education.